Corporate governance and default risk in long-term conventional bonds and sukuk in Malaysia - Saad N.M.; Haniff M.N.; Ali N. (Serials Publications, 2023)
The presence of key institutional investors/owners and BOD characteristics as highlighted by Malaysian Code on Corporate Governance (MCCG) may have influence on the yield to maturity (YTM) of bonds and sukuk. It is argued that higher institutional ownerships will produce enhanced active monitoring on cost of debt and presumably more control on the likelihood of default risk occurrence as measured by the size of yield spreads for conventional bonds and sukuk. Agency theory also explains the relationship between principal and agent and the possible misalignment of interest of both parties is reflected through the incurrence of what is termed as agency cost. To reduce this agency cost requires the necessity of incurrence of cost of monitoring and controlling by the principal which in large firms is represented by institutional investors which delegated this responsibility to the appointed board of directors (BOD). Thus, the main objective of this study is to investigate the relationship between these corporate governance mechanisms with respect to institutional investors and BOD characteristics with the default risk as proxy by yield spread of bond and sukuk in Malaysia. The data are obtained from firm issuers' annual reports, Bondinfo Hub of Malaysian Central Bank, Malaysian Department of Statistics and Bloomberg databases for the period beginning 2000 to 2014. Unbalanced panel data are applied for the tests which cover the pooled ordinary least square (OLS), fixed effects (FE) and random effects (RE) models. The results suggest that the presence of institutional ownerships does have an inverse relationship on the default risk for long-term sukuk. However, the results do not support any relationship between institutional ownerships and long-term conventional bonds defaults. Mixed result reveal by BOD characteristics.